Development in Africa and Agricultural Innovation - Kasey Miller; Glenn Shinn (Journal of International Agricultural and Extension Education, 2012)
On the world stage, Africa is a diverse continent of contrasts and misconceptions. Juma is a well-qualified author with roots in Kenya and significant experience, including as professor of practice of international development at the Harvard University John F. Kennedy School of Government and director of the Science, Technology, and Globalization Project. Juma is widely recognized for his practical work on sustainable development.
Keywords: Africa; Agricultural Development; Capacity Building; Education; Entrepreneurship; Infrastructure; Innovation; Technologies; Women